Making robot’s attitudes predictable: a stereotype content model for human-robot interaction in groups - Oliveira, R. (2018)
Stereotypes play a key role both in human and in robot perception. As such, these may play an important role in predicting behavior towards the targets of said stereotypes. In this paper, we argue for the usefulness of exploring how stable dimensions of stereotype content, more specific?ally warmth and competence, apply to HRI. We propose to do so by examining the impact of these characteristics, displayed by robots, on the emotions, behaviors and future intention of participants to interact and work with robots. We chose these two stereotypical dimensions given that research has demonstrated their underlying and ubiquitous influence on people perception and responses. Moreover, we decided to explore this issue in the context of small group interactions due to the ever-common nature of this type of social arrangements in people’s everyday life.